(untitled) (International relations and international law Journal, 2022)
The particular danger of extremism lies in the fact that the majority of new members of recruitment to extremist organizations consists of young people. Therefore, in this work the authors attempt to explore the previously unexplored topic of the relationship between the propensity of young people to extremism and the features of the nonverbal reactions they demonstrate. In determining the modern principles of nonverbal behavior research, attention is focused on the fact that the interpretation of nonverbal behavior of a person should include the context of an individual’s basic behavior model, taking into account specific circumstances and observing the dynamics of changes in verbal and nonverbal behavior of the individual. The spread of youth extremism is explained by the insufficient sexual and age maturity of young people, the lack of their emotional stability in the face of the negative impact of media content and social networks, the development of trends in recruiting new members through social networks and other electronic platforms. In the practical section of the article authors discuss state and public programs which counter various forms of extremism among young people. When discussing the results, authors make a conclusion about the multifaceted manifestation of the influence of extremism on the young population and criticize the current lack of research combining the study of nonverbal reactions of people and their propensity to extremism. As a further perspective for the development of measures to counteract extremism, it is proposed to conduct empirical interdisciplinary research in the field of the relationship between nonverbal behavior and youth extremism.